Local Wisdom–Based Educational Management: Integrating Cultural Values into School Governance - Rizky Al Fajri; Risfa Tri Ulfa; M. Syukron Maksum; Salis Masruhi (Al-Qalam Institue, 2026)
This study aims to analyze a local wisdom–based educational management model at SDN 96/X Rantau Indah and its effectiveness in enhancing student engagement, motivation, and knowledge construction. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using interactive techniques involving data reduction, data display, and conclusion drawing. The findings indicate that the integration of local cultural values is implemented through three main pillars: curricular integration, co-curricular activities, and school culture, which collectively foster meaningful and contextually relevant learning practices. Local wisdom serves as cognitive scaffolding, enabling students to actively construct knowledge by connecting academic concepts with cultural experiences. Teachers’ roles transform into facilitators and cultural mediators linking the national curriculum with local values, while collaborative social interactions reinforce knowledge construction. The model is effective in improving students’ motivation and academic understanding. However, challenges include uneven teacher competencies, limited time to align national and local curricula, and sustainability of community involvement. Strengthening educational management, teacher professional development, and formal partnerships between schools and local communities are essential to sustain local wisdom integration.